Performance Analysis of US Hedge Funds - Kamdar, Tanvi (2012)
The aim of this dissertation is to investigate the strategies employed by successful hedge funds and analyse these funds’ performance on the basis of those strategies. This research is done to throw light on the performance analysis of hedge funds strategies, the implementation of these strategies, their benefits and the risk involved in them. The returns of hedge funds over the period of 1994-2010 reported by the Hennessee Hedge Fund Index have been analysed using absolute performance measure like the Sharpe Ratio.